Economics for today's world - Tucker, Irvin B. (Thomson/South-Western, 2008)
The first two chaptes introduce you to a foundation of economic knowledge vital to understanding the other chapters in the text. In these introductory chapters you will begin to learn a valuable reasoning approach to solving economics puzzles that economicst call " the economic way of thinking",...